2010
DOI: 10.1007/s11605-010-1318-4
|View full text |Cite
|
Sign up to set email alerts
|

The Preoperative Manometric Pattern Predicts the Outcome of Surgical Treatment for Esophageal Achalasia

Abstract: This is the first study by a surgical group to assess the outcome of surgery in 3 manometric achalasia subtypes: patients with panesophageal pressurization have the best outcome after laparoscopic Heller-Dor myotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
158
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(172 citation statements)
references
References 27 publications
(35 reference statements)
9
158
1
4
Order By: Relevance
“…One of the original observations with the description of achalasia phenotypes was that treatment outcome was dependent on phenotype, with outcomes being best in type II and probably worst in type III 18 . Those observations have subsequently been confirmed by a number of other studies [21][22][23] (TABLE 3).…”
Section: Achalasia With Preserved Peristalsissupporting
confidence: 68%
See 1 more Smart Citation
“…One of the original observations with the description of achalasia phenotypes was that treatment outcome was dependent on phenotype, with outcomes being best in type II and probably worst in type III 18 . Those observations have subsequently been confirmed by a number of other studies [21][22][23] (TABLE 3).…”
Section: Achalasia With Preserved Peristalsissupporting
confidence: 68%
“…3). In multiple reported HRM series from major centers worldwide, type II achalasia is the most common subtype 18,[21][22][23] . Paradoxically, type II achalasia would often go undetected or misdiagnosed with conventional manometry because of LES pseudo relaxation during pan-oesophageal pressurization, or because panoesophageal pressurization was mistaken for a spastic contraction, resulting in an alternative diagnosis of distal oesophageal spasm.…”
Section: Achalasia Phenotypesmentioning
confidence: 99%
“…In addition, several authors have also reported similar patient outcomes after myotomy even after prior failed pneumatic dilation or Botulinum toxin injections Surgery after botulinum toxin injections has been suggested to be more difficult because of a marked fibrotic reaction that can develop at the gastroesophageal junction that obliterates surgical planes (62)(63)(64)(65). Nevertheless, some authors have reported similar outcomes in this situation to those of a primary procedure (66)(67)(68).…”
Section: Heller Myotomymentioning
confidence: 82%
“…There is no difference in clinical success rates between PD and LHM for patients with types I and type II achalasia, but the type III pattern responds better to surgery than to PD, probably because of the more extensive proximal disruption of the esophageal muscle (63).…”
Section: Heller Myotomymentioning
confidence: 87%
See 1 more Smart Citation